2019
DOI: 10.1002/celc.201900101
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Liquid/Poly(vinylidene fluoride‐co‐hexafluoropropylene) Gel‐Polymer Electrolyte with a Compatible Interface for Sodium‐Based Batteries

Abstract: Ionic liquid gel-polymer electrolytes (GPEs) have attracted increasing attention, owing to their merits of safety and reliability. However, the high viscosity of ionic liquid requires better transmission channels for the polymer. Exploration of ionic liquid GPEs with high ionic conductivity and excellent transmission channels is a possible strategy to optimize the practicability of sodium-based technology. A flexible GPE with high ionic conductivity and excellent transmission channels is synthesized with poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Ionic liquids, with the merits of nonflammability, high ionic conductivity, and good electrochemical stability, are suitable plasticizers for preparing GPEs. [ 137,145–148 ] Pyrrolidinium‐based ionic liquids combining with TFSI − or FSI − were widely applied owing to their high antireducibility. It has been demonstrated that the Pyr 13 TFSI or Pyr 13 FSI ionic liquids could suppress the crystallization of PEO, [ 149–152 ] which had a distinct plasticizing effect on the polymer, but the plasticizing mechanism was seldom discussed.…”
Section: Pes For Na‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids, with the merits of nonflammability, high ionic conductivity, and good electrochemical stability, are suitable plasticizers for preparing GPEs. [ 137,145–148 ] Pyrrolidinium‐based ionic liquids combining with TFSI − or FSI − were widely applied owing to their high antireducibility. It has been demonstrated that the Pyr 13 TFSI or Pyr 13 FSI ionic liquids could suppress the crystallization of PEO, [ 149–152 ] which had a distinct plasticizing effect on the polymer, but the plasticizing mechanism was seldom discussed.…”
Section: Pes For Na‐ion Batteriesmentioning
confidence: 99%
“…As a PE matrix, it exhibits excellent properties, including high mechanical strength, electrochemical stability, thermal stability, etc. [ 147,153–155 ] Lately, Janakiraman et al. [ 156 ] prepared a PVDF‐based GPE for SIBs by electrospinning method with a nanofibers structure, which exhibited a wide voltage window (0–5 V vs Na + /Na) and high ionic conductivity of 1.08 × 10 −3 S cm −1 .…”
Section: Pes For Na‐ion Batteriesmentioning
confidence: 99%
“…A particular advantage of IL-based GPEs is the high thermal stabilities of the membranes that can be obtained. For example, Xie and co-workers incorporated the IL N-methyl-N-butylpiperidine difluoromethylimide into poly­(vinylidene fluoride-co-hexafluoropropylene) membranes to make GPEs for Na-ion batteries that were thermally stable up to 450 °C . Zheng and co-workers formed poly­(vinyl alcohol)-based membranes containing ammonium-based ILs for use as proton exchange membranes, which were stable up to 160 °C, considerably higher than that achievable using conventional membranes (∼80 °C) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie and co-workers incorporated the IL N-methyl-Nbutylpiperidine difluoromethylimide into poly(vinylidene fluoride-co-hexafluoropropylene) membranes to make GPEs for Na-ion batteries that were thermally stable up to 450 °C. 13 Zheng and co-workers formed poly(vinyl alcohol)-based membranes containing ammonium-based ILs for use as proton exchange membranes, which were stable up to 160 °C, considerably higher than that achievable using conventional membranes (∼80 °C). 14 Langevin and co-workers synthesized proton-conductive GPEs that could operate at 130 °C, by incorporating triethylmethylammonium trifluoromethanesulfonate into polyimide membranes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, safety concerns can arise from the flammability of such organic solvents and the potential hazards of electrolyte leakage. One of the most promising methods to mitigate such safety risks would be to adopt a nonflammable liquid electrolyte or a solid-state electrolyte for SIBs. …”
Section: Introductionmentioning
confidence: 99%